CHILD AND PARENT RELATIONS IN THE FAMILY - Bahauddinov Shamsuddin Salievich (International Engineering Journal For Research & Development, 2021)
This article provides recommendations for educating young people. In particular, the responsibilities of parents in the upbringing of young people were revealed. Aspects of parenting in parenting were outlined. Existing problems in the upbringing of young people were pointed out. The solutions to these problems are based on Islamic sources. Data were obtained from reliable sources.